2021
DOI: 10.1038/s41598-021-91129-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential and challenges of specifically isolating extracellular vesicles from heterogeneous populations

Abstract: Extracellular vesicles (EVs) have attracted interest due to their ability to provide diagnostic information from liquid biopsies. Cells constantly release vesicles divers in size, content and features depending on the biogenesis, origin and function. This heterogeneity adds a layer of complexity when attempting to isolate and characterize EVs resulting in various protocols. Their high abundance in all bodily fluids and their stable source of origin dependent biomarkers make EVs a powerful tool in biomarker dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…The diversity of the mechanisms that lead to the release of small particles from cells contributes to the heterogeneity of the isolated material, which often contains populations of submicron particles of variable compositions and morphologies. Nowadays, it is well known that the field of EV studies suffers from poor reproducibility and inadequacy in terms of the separation of (and appropriate assignation of specific effects to) vesicles, lipoproteins, large protein complexes/aggregates, and other assemblies of biomolecules with similar/overlapping size and physico-chemical properties [ 26 ]. The system-interfering analytics and indirectness of the evidence also limit the relevance of the studies from the perspective of pursuing natural pathways (in vivo occurring processes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of the mechanisms that lead to the release of small particles from cells contributes to the heterogeneity of the isolated material, which often contains populations of submicron particles of variable compositions and morphologies. Nowadays, it is well known that the field of EV studies suffers from poor reproducibility and inadequacy in terms of the separation of (and appropriate assignation of specific effects to) vesicles, lipoproteins, large protein complexes/aggregates, and other assemblies of biomolecules with similar/overlapping size and physico-chemical properties [ 26 ]. The system-interfering analytics and indirectness of the evidence also limit the relevance of the studies from the perspective of pursuing natural pathways (in vivo occurring processes).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small size of EVs and their heterogeneity in terms of size and composition, the quantification of EVs is still a challenge [ 23 , 24 ]. In addition, the properties of the isolated material strongly depend on the method of isolation [ 25 , 26 , 27 , 28 ]. Even when the same type of equipment and protocols are used, the reproducibility of isolation tends to be poor [ 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Allelein et al confirmed, heterogenous populations vary greatly. This phenomenon must exist in clinical samples [144]. In order to overcome these bottlenecks, we suggest that more studies need to sort out detailed information, including source cell type, extraction method, purity, modified vesicle type, etc.…”
Section: Current Combinations and Clinical Trials Of Ev-based Carriersmentioning
confidence: 99%
“…The vesicles size is varied and ranges from 30 nm to 5 μm. Although EVs have a similar structure, there are major differences regarding the mechanism of their formation and physicochemical properties [ 80 , 81 , 82 , 83 ]. Apart from the density, isolation methods, or the presence of specific markers, the size and diameter of the vesicles are the most common EVs classification criteria.…”
Section: Extracellular Vesicles Secretion Accompanying the Endothelium Destruction Processesmentioning
confidence: 99%
“…The mechanism of initiation and the course of migration depends on many complex processes, among which migration is the most important. It plays a key role in embryonic development but is also responsible for the movement of immune cells, wound healing, and tissue regeneration [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Cell movement is also a pivotal factor during the formation of tumor metastases and in the course of inflammation.…”
Section: Extracellular Vesicles Secretion Accompanying the Endothelium Destruction Processesmentioning
confidence: 99%